2007
DOI: 10.1002/bmc.776
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the characterization of Jet Propellent‐8: vapor and aerosol

Abstract: Jet Propellant-8 (JP-8) has been responsible for the majority of reported chemical exposures by the US Department of Defense. Concerns related to human exposure to JP-8 are relatively new; therefore, there is a lack of literature data. Additionally, health effects related to the composition of the exposure have only recently been considered. Two major questions exist: (1) what is the compositional difference between the aerosol and vapor portions of JP-8 under controlled conditions and (2) what is the most rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Among C−H bond cleavages, the most favorable one occurs from the α carbon in the side chain producing 1-phenyl-but-1yl with an energy loss of 369 kJ mol −1 . The other H losses from sp 3 carbon atoms require higher energies of 411, 408, and 420 kJ mol −1 and forming the corresponding 2-yl, 3-yl, and 4-yl 1phenyl-butyl radicals, respectively. We do not consider here the ruptures of C−H bonds on the sp 2 carbons of the aromatic ring, which are unlikely to compete because their bond energies are typically much higher, e.g., 466 kJ mol −1 for benzene.…”
Section: Resultsmentioning
confidence: 99%
“…Among C−H bond cleavages, the most favorable one occurs from the α carbon in the side chain producing 1-phenyl-but-1yl with an energy loss of 369 kJ mol −1 . The other H losses from sp 3 carbon atoms require higher energies of 411, 408, and 420 kJ mol −1 and forming the corresponding 2-yl, 3-yl, and 4-yl 1phenyl-butyl radicals, respectively. We do not consider here the ruptures of C−H bonds on the sp 2 carbons of the aromatic ring, which are unlikely to compete because their bond energies are typically much higher, e.g., 466 kJ mol −1 for benzene.…”
Section: Resultsmentioning
confidence: 99%
“…Jet fuel JP-8 contains more shorter-chain hydrocarbons in the vapour phase and more longer-chain hydrocarbons in the aerosol phase, but the fraction of C13-C17 compounds in the aerosol is at the most twice as high as in the liquid. The limit of depletion/accumulation is about C12 (JP-8; Gregg et al 2007). The concentration is determined based on the sum of the CH compounds from C9 to C16; the vapour saturation concentration of n-C14 is only 15 ml/m 3 and the vapour saturation concentrations of n-C15 and n-C16 are even lower.…”
Section: Distillates (Petroleum) Hydrotreated Lightmentioning
confidence: 99%
“…In another study, 37 compounds were identified from JP-8 neat fuel, vapor and aerosol (Gregg et al, 2006). These compounds were identified using retention time matches with authentic standards and by comparison to EI mass spectra from databases.…”
Section: Jp-8 Exposurementioning
confidence: 99%